Reefer container monitoring system based on WSN and cloud technology - Peiyao Tang (2019)
Reefer containers are the main transportation method for the import and export of food and medicine. For high-quality products is necessary to monitor the condition of the reefer containers in order to avoid affecting goods quality due to environmental variations. Monitoring the reefer containers which are used to transport fruits, vegetables, and dairy products is one of the examples. In this context appears the necessity to develop this work expressed by a distributed sensor system for monitoring reefer containers. With the support of the WSN (wireless sensor network) including a set of sensors, it is possible to obtain the information about the temperature, humidity and location data of the reefer container and upload those data to a cloud platform expressed in the case of the purposed system by The Things Network platform. Based on LEACH (Low Energy Adaptive Clustering Hierarchy) routing algorithm, the embedded software was developed to guarantee a well-balanced distribution of the energy load among WSN end-nodes. A web application and a mobile application has been developed to display the data coming from the WSN node. To check if the reefer container working in a good condition, an alarm software module has been developed to highlight abnormal data coming for the system. The routing algorithm has been simulated and the effectiveness of the algorithm is verified by simulation results. The effectiveness of the proposed system was experimentally tested, and several results are included in this dissertation.